(untitled) (Journal of Epidemiology and Public Health, 2023)
Background: Overweight or obesity is a public health problem worldwide which is increasing both in the general population and in people with chronic diseases. Overall both children and adults are vulnerable to overweight or obesity. This study aims to examine the effect of physical activity, consumption of vegetables and alcohol on overweight or obesity using a meta-analysis. Subjects and Method: Meta-analysis was carried out using the PRISMA flowchart and the PICO model. Population: age 6 to 64 years. Intervention: low physical activity, low vegetable and fruit consumption, and high alcohol. Comparison: high physical activity, high vegetable and fruit consumption, and alcohol low. Outcome: overweight or obese. The databases used are Google Scholar, PubMed, and Proquest with keywords (Overweight OR Obesity OR "BMI Status") AND (“Physical Activity” OR Exercise OR Sport OR Inactive) AND (Vegetable AND Fruit) AND Alcohol AND "Cross Sectional" AND aOR. There were 22 cross-sectional studies published in 2012-2022 that met the inclusion criteria. Analysis was performed with RevMan 5.3. Results: A meta-analysis was conducted on 22 articles with a cross-sectional study design originating from Indonesia, Ghana, Arab Emirates, Texas, Ethiopia, Uganda, Botswana, Congo, Bahir Dar, North Western, Toronto, Zambia, Cameroon and Tanzania involving 91,031 ages 6-64 years. The results of the meta-analysis showed that someone with low physical activity had a risk of being overweight or obese 1.35 times compared to high physical activity (aOR= 1.35; 95% CI= 1.09 to 1.68; p<0.001), someone with high consumption of vegetables and fruit have a risk of experiencing overweight or obesity 1.40 times compared to high consumption of vegetables and fruits (aOR= 1.40; 95%CI= 0.94 to 2.08; p<0.001), and someone with high alcohol has a risk of experiencing overweight or obesity 1.47 times compared low alcohol (aOR= 1.47; 95% CI= 1.31 to 1.65; p<0.001). Conclusion: Low vegetable and fruit consumption, high alcohol consumption and low physical activity can increase the risk of being overweight or obese. Keywords: social support, self-efficacy, social cognitive theory, hypertension, medication adherence Correspondence: Dena Tri Solehaini. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: dena35tri@gmail.com. Mobile: +6282329210977.